Dietary supplementation with Salvia sahendica attenuates acetylcholinesterase activity and increases mitochondrial transcription factor A and antioxidant proteins in the hippocampus of amyloid beta‐injected rats. (25th July 2013) - Foolad, Forough; Khodagholi, Fariba
Abstract: Objectives: We evaluated the acetylcholinesterase (AChE) inhibitory and potential antioxidant effects of Salvia sahendica extract to investigate whether these molecules are involved in learning and memory improvement in rats injected with fibrillar amyloid beta (Aβ) peptide in the CA1 region of their hippocampus. Methods: Rats were fed with S. sahendica (100 mg/kg/day) for 1 week before Aβ injection. Western blot analysis and enzymatic assays were carried out 7 days after injections. Key findings: Our results indicated that S. sahendica extract decreased AChE activity. Besides, S. sahendica prevented reduction in the level of nuclear respiratory factor‐1 and mitochondrial transcription factor A (TFAM). Our data indicated the lack of sensitivity in citrate synthase and reduction in the activity of malate dehydrogenase in the presence of Aβ that was prevented with S. sahendica consumption. Pretreatment with S. sahendica extract impeded reduction of glutathione redox ratio, catalase and superoxide dismutase activity, while decreased the malondialdehyde level. Conclusions: Based on the importance of AChE activity inhibition and increased TFAM level in the prevention of cognitive impairment, the use of S. sahendica could open a new protective issue in therapeutic fields of neurodegenerative disease.